Bipolar zinc-ion battery

Through the stacked structure design of bipolar zinc ion batteries and the use of porous isolation films, the problems of existing zinc-manganese batteries being unable to charge and discharge, high cost and insufficient safety are solved, and low-cost, high safety and high power zinc ion batteries are realized.

CN110690512BActive Publication Date: 2025-04-18BANGTAIHONGTU SHENZHEN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201911018868.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-10-24
Publication Date
2025-04-18
Estimated Expiration
2039-10-24

AI Technical Summary

Technical Problem

Existing zinc-manganese batteries cannot achieve charging and discharging, which is costly and insufficient safety. The traditionally designed stainless steel mesh current collector results in high resistance, low power, and difficult to seal and adapt to expansion of battery materials.

Method used

The bipolar zinc ion battery design is adopted to form a sealed battery cell through the laminated structure of anode plastic current collector, isolation film and cathode plastic current collector, and the movement of zinc ions is achieved using porous isolation film and zinc compound electrolyte, and the resistance is reduced through the plastic current collector.

Benefits of technology

Rechargeable and dischargeable zinc ion batteries are realized, reducing costs and resistance, improving safety and sealing, adapting to the expansion of battery materials, and improving power design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110690512B_ABST
    Figure CN110690512B_ABST
Patent Text Reader

Abstract

The present invention discloses a bipolar zinc ion battery, comprising at least one unit group, wherein the unit group comprises at least one battery unit; the battery unit comprises: an anode plastic current collector, a separator and a cathode plastic current collector which are stacked in sequence and mutually bonded and sealed on all sides, a cathode active material layer arranged on the inner side of the cathode current collector as a cathode, an anode active material layer arranged on the inner side of the anode current collector as an anode, an electrolyte infiltrated in the gaps between the cathode, the anode and the separator film, which contains a zinc compound, and a porous ion channel arranged on the separator between the cathode and the anode for the movement of zinc ions. The present invention has a simple structure, light weight, and good safety performance and usability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery, in particular to a plastic current collector bipolar zinc ion battery. Background Art

[0002] The large-scale application of fossil fuels has led to great prosperity throughout the 20th and 21st centuries, but it has also led to excessive emissions of greenhouse gases, which in turn has led to global warming; the development of new energy is based on this general background. The large-scale development and application of wind energy, solar energy, etc. has further reduced the price of new energy, and there is no cost barrier for large-scale promotion, but the instability of its output has an impact on the power grid and has also led to many wind and solar power abandonment incidents. Unstable new energy requires energy stabilizers and energy mixers, and batteries are the most ideal energy stabilizers and mixers.

[0003] However, conventional lithium-ion batteries are expensive and require a lot of redundancy in safety management. Therefore, large-scale energy storage must seek lower-cost and safer battery technology.

[0004] Conventional zinc-manganese batteries use MnO2 as the positive electrode, zinc metal as the negative electrode, and an aqueous solution as the electrolyte, so their cost can be made low and safe. However, conventional zinc-manganese batteries are used as primary batteries and cannot be recharged, or the charging efficiency is very low.

[0005] Conventional zinc-manganese batteries use zinc foil or stainless steel mesh as current collectors, and then the cathodes are connected in parallel, and the anodes are connected in parallel to form a battery. This design is relatively traditional. Since stainless steel mesh is used as the current collector, its resistance is high, the power is low, and it is easy to have steel mesh burrs and other phenomena, so thicker diaphragm paper is required to match it.

[0006] Therefore, how to provide a battery technology that is rechargeable, safe, simple in structure, simple in process, and low in cost is a technical problem that needs to be solved urgently in the energy storage industry. Summary of the invention

[0007] In order to solve the above technical problems in the prior art, the present invention proposes a bipolar zinc ion battery.

[0008] Bipolar battery

[0009] Bipolar batteries use a design in which multiple individual electrochemical cells are stacked with bipolar plates connecting the electrochemical cells in series. Typically, each bipolar plate has a positive electrode material on a first side of the bipolar plate and a negative electrode material on a second side of the bipolar plate. In this way, when a bipolar plate separates two adjacent electrochemical cells, it serves as a negative current collector plate for one electrochemical cell and as a positive current collector plate for a second electrochemical cell. The bipolar plates allow current to flow between adjacent electrochemical cells during charging and discharging, and also provide electrochemical isolation between the electrochemical cells so that no ion flow occurs between adjacent electrochemical cells through the bipolar plates. Compared to conventional monopolar battery cells (where metal tabs are used to connect the current collector plates of battery cells connected in series), electrons travel very short distances on the bipolar plates, rather than traveling outside the cell through metal tabs. This can result in more uniform current density and higher power designs.

[0010] In traditional bipolar battery designs, because the cathode and anode share the same metal current collector, they are difficult to seal when stacked together. It is also difficult to adapt to the expansion of battery materials and battery cells, and it is not easy to detect problems or defects in each layer.

[0011] The bipolar zinc ion battery of the present invention comprises at least one cell group, wherein the cell group comprises at least one battery cell;

[0012] The battery cell comprises: the battery cell comprises: an anode plastic current collector, a separator and a cathode plastic current collector which are stacked in sequence and bonded and sealed to each other on all sides to form two cavities, a cathode active material layer arranged on the inner side of the cathode current collector as a cathode, an anode active material layer arranged on the inner side of the anode current collector as an anode, an electrolyte infiltrated in the gaps between the cathode, the anode and the separator membrane, which contains a zinc compound, and a porous channel arranged on the separator between the cathode and the anode for the movement of zinc ions.

[0013] Specifically, the inner side of the anode current collector layer is coated with an anode material layer containing zinc powder or a composite zinc foil layer as an anode.

[0014] Preferably, the surface of the zinc foil layer or the surface of each particle of the zinc powder is coated with an organic coating or an inorganic coating, or a coating of a mixture of organic and inorganic substances.

[0015] Preferably, the cathode active material contains nano manganese tetroxide particles, and / or the cathode active material is doped with Ni, Co, Al, Mg, Fe, V or Cu, and the surface of the manganese tetroxide particles is coated with a carbon nanotube layer, a carbon layer or a graphene layer.

[0016] Specifically, the isolation membrane layer includes a porous region located in the middle and including the porous channel, and a frame region located around the porous region, the area of ​​the porous region is larger than the area of ​​the anode and the cathode, so that the four sides of the porous region exceed the four sides of the cathode and the anode opposite to it, and the area of ​​the isolation membrane layer is larger than the anode current collector layer and the cathode current collector layer, so that the four sides of the frame region are exposed to the anode current collector layer and the cathode current collector layer after being bonded to the anode fluid layer and the cathode current collector layer.

[0017] Preferably, the isolation membrane layer is made of a porous substrate, and the frame region is made of a porous substrate filled with a polymer.

[0018] Preferably, the anode current collector layer and the cathode current collector layer are coated with a conductive pre-coating layer for bonding the anode and cathode electrode layers, respectively.

[0019] Specifically, when the cell group includes two or more battery cells, the anode current collector layers and cathode current collector layers of adjacent battery cells are attached to each other and connected in series.

[0020] Specifically, when the bipolar zinc ion battery comprises two or more unit groups, the unit groups are stacked along the stacking direction of the battery cells, and an insulating layer is provided between adjacent unit groups, and all unit groups are connected in parallel through current collectors.

[0021] Specifically, a metal outer hoop layer is provided on the periphery of the bipolar zinc ion battery to prevent the battery from expanding along the stacking direction of the cell group, and an insulating layer is provided on the portion of the metal outer hoop layer that contacts the cell group.

[0022] The zinc ion battery of the present invention has simple process and structure, low cost, and can be well sealed. The gel electrolyte of the water solvent is used to prevent leakage. Moreover, the present invention does not use all-metal as the current collector, so the product quality will be lighter. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention is described in detail below with reference to the embodiments and accompanying drawings, wherein:

[0024] Figure 1 Schematic diagram of the structure of the first embodiment of the battery unit of the present invention.

[0025] Figure 2 Schematic diagram of the structure of the second embodiment of the battery unit of the present invention.

[0026] Figure 3 It is a schematic diagram of the structure of zinc powder particles of the present invention.

[0027] Figure 4 It is a schematic diagram of the structure of manganese tetraoxide particles of the present invention.

[0028] Figure 5 It is a schematic diagram of the stacking structure of the first battery unit of the present invention.

[0029] Figure 6 It is a schematic diagram of the stacking structure of the second battery unit of the present invention.

[0030] Figure 7 It is a schematic diagram of the stacked structure of the unit group of the present invention.

[0031] Figure 8 It is a partial dimension diagram of the battery unit of the present invention. DETAILED DESCRIPTION

[0032] The principles and embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0033] The bipolar zinc ion battery of the present invention comprises at least one unit group, and each unit group comprises at least one battery cell.

[0034] The battery cell 1 of the present invention can have two structures. Figure 1 , Figure 2 Two embodiments of the battery cell of the present invention are respectively shown.

[0035] like Figure 1 As shown, in the first embodiment, the battery cell 1 of the present invention includes: an anode current collector layer 11, a separator layer 12, a cathode current collector layer 13, a cathode 15, an anode 14 and an electrolyte (not shown in the figure). The anode current collector layer, the separator layer and the cathode current collector layer are all made of flexible materials. For example, the anode current collector layer 11 and the cathode current collector layer 13 are made of a plastic film made of PP, PE, PU, ​​PIB or PET and a conductive agent, or a conductive film formed by mixing polypropylene PP, polyethylene PE, polyurethane PU, polyisobutylene PIB, polyethylene terephthalate PET with carbon black, or a conductive film formed by using carbon nanotubes CNT, or a plastic film containing carbon black or carbon nanotubes electroplated with one or more metals such as Cu, Ni, Ti, Al, Fe, Cr, etc. The film of the anode current collector layer 11 and the cathode current collector layer 13 can be formed by extrusion, stretching, casting or rotary cutting, and can also be called a polymer current collector layer (PCC). The resistivity of PCC is about 10 -5To 1 ohm.m, the thickness is about 10-100um, it can selectively permeate O2 and H2, but H2O is impermeable. The anode current collector layer 11 and the cathode current collector layer 13 are used to coat or bond the anode and cathode. The area can be further provided with an electrode conductive pre-coating layer. The thickness of the electrode layer conductive coating is 2-5um, and the resistivity is around 10-3 to 1Ohm.m. It can be made of PTFE, PIB or PVDF, CMC and carbon black, graphene or carbon nanotubes mixed with conductive agents or other low-temperature activated adhesives. The isolation film layer uses PP, PET, PE, PI or other polymer materials as the substrate. It is a porous film with a pore size of 10-2000nm and a porosity of 20%-90%. The surface of the substrate is treated by plasma or chemical methods to form more -OH, which will make the isolation film layer have better water wettability, more water absorption and better liquid retention. The center of the substrate is a porous area for the movement of zinc ions. One side of the porous area of ​​the substrate is coated with ceramics (such as Al2O3, Al2O3-H2O, TiO2, etc.) and a binder to inhibit zinc metal dendrites and enhance adhesion. The other side of the substrate is coated with a binder (SBR, PVDF, PTFE, PIB, etc.) to enhance adhesion. The frame area located around the porous area is coated with an adhesive on both sides to bond the anode current collector layer 11 and the cathode current collector layer 13 to seal the battery. The frame area can be made of a porous base material filled with a polymer to fill the pores, or the frame area can be directly closed by hot pressing.

[0036] Then the anode current collector layer 11, the separator layer 12 and the cathode current collector layer 13 are stacked in sequence, and the adhesive on both sides of the frame area of ​​the separator layer 12 is used to seal the four sides to form two cavities. The anode and the cathode are respectively arranged in the two cavities, wherein the cathode is composed of a cathode active material layer arranged on the inner side of the cathode current collector layer, and the anode is composed of an anode material layer or a zinc foil layer containing zinc powder coated on the inner side of the anode current collector layer 11. The electrolyte containing the electrolyte is evenly distributed in the pores of the separator, the cathode and the anode. The electrolyte contains zinc compounds, and the porous area is provided with a plurality of holes for zinc ions to move through. During the charge and discharge process, the zinc ions will move between the cathode and the anode through these holes.

[0037] Since the anode current collector layer and the cathode current collector layer are made of plastic material, the surface between the electrode attachment area (anode or cathode) and the sealed edge is a smooth curved surface, such as Figure 8 As shown at position A in Figure 8Position B in the figure is the sealing area of ​​the anode current collector layer, the cathode current collector layer and the isolation film layer. The left edge of the sealing area is less than 0.1 mm from the edge of the anode current collector layer or the cathode current collector layer, the right edge of the sealing area is more than 1 mm from the edge of the anode current collector layer or the cathode current collector layer, and the edge of the isolation film layer is within 0.1 mm more than the edge of the anode current collector layer or the cathode current collector layer. In this embodiment, the edge of the anode is within 0.1 mm more than the edge of the cathode.

[0038] like Figure 3 As shown, the surface of the zinc powder particles 19 can be treated to form a coating 20. By applying an inorganic coating, the surface stability can be improved and the formation of dendrites during the charge and discharge process can be suppressed. Specifically, the surface of the zinc powder particles can be coated with Al2O3, SiO2, TiO2, CaO, MgO, ZnO, ZnF2, ZnCl2, and ZnCO3. The surface stability can also be improved and the growth of dendrites can be suppressed by applying an organic coating. Specifically, the surface of the Zn particles or zinc foil can be coated with PA (CA (citric acid), PEGPE, PEO, etc.). Of course, it can also be a coating of an organic and inorganic mixture, for example, a ZnO mixture with PA or CA. In a specific embodiment, we use a zinc alloy as the anode material. A zinc alloy with Bi, Sn, Cu, and In elements as the anode material will help suppress the release of O2 and H2. The specific formula of the anode material can be 95% zinc powder, 4% PVDF and 1% carbon nanotubes, or 96% zinc powder, 2% CMC, 2% SBR and 1% carbon nanotubes, or 96% zinc powder, 3% PTFE and 1% carbon nanotubes, or 95% zinc powder, 3% PIB, 1% graphite and 1% carbon nanotubes.

[0039] like Figure 4As shown, the cathode active material contains manganese tetraoxide particles 16, and / or the cathode active material is doped with Ni, Co, Al, Mg, Fe, V or Cu and other doped particles 18, the size of the manganese tetraoxide particles 16 is about 10nm-20um, we can treat its surface to improve the electronic conductivity, specifically, the surface of the manganese tetraoxide particles can be coated with carbon nanotube layers, carbon layers or graphene layers. The thickness of these coating layers 17 is 0.1-1nm, and these coatings form a 3D mesh structure, which can be a coating made by a physical method or a coating made by a chemical method. Another way of surface treatment is also to improve the surface stability, we can coat Al2O3, MgO, and the manganese tetraoxide can be mixed with dopants, such as Ni, Co, Al, Mg, Fe, V or Cu, and the proportion of doping can be a mixture of one or more of the listed materials within 10% to improve the stability of the structure. The formula of the cathode material layer can be: 95% manganese tetraoxide, 4% PVDF and 1% carbon nanotubes, or 96% manganese tetraoxide, 2% CMC, 2% SBR and 1% carbon nanotubes, or 96% manganese tetraoxide, 3% PTFE and 1% carbon nanotubes, or 95% manganese tetraoxide, 3% PIB, 1% graphite and 1% CNT.

[0040] The electrolyte of the present invention adopts ZnSO4, MnSO4 and zinc methanesulfonate mixture (C2F6O6S2Zn) ZnBOB as electrolyte, pure water as solvent, pH value is controlled between 6-8, Zn ion concentration is between 0.5-10mol / L, Mn ion concentration is between 0.1-10mol / L, gel material uses copolymer of CMC or PEO or VDF, and further can use electrolyte additives such as VC, FEC or additives for low voltage reduction to improve the cycle life of the battery. Because the electrolyte adopts water solvent, the zinc ion battery of the present invention has a good fireproof effect.

[0041] like Figure 2As shown, in the second embodiment, the battery cell of the present invention includes an anode current collector layer 11, a separator layer 12, a cathode current collector layer 13, a cathode 15 and an electrolyte (not shown in the figure). In this embodiment, the anode current collector layer 11 is used as the anode, and there is no pre-coated zinc layer. During the first charge, the electrolyte will deposit zinc on the anode current collector layer 11 to form an anode. Other structures such as the separator layer, the electrolyte, the cathode, etc. are the same as those in the first embodiment. This embodiment has sufficient void space for gas accumulation during overcharge or overdischarge, and both the heat seal and the adhesive can select permeability to allow H2 and O2 to release, but not allow H2O to penetrate out, or a one-way valve that can release pressure is provided on the sealing area of ​​the battery. When the internal pressure accumulates to a certain pressure (for example, 0.01-0.05Mpa higher than atmospheric pressure), the pressure is released. The width of the isolating film layer is wider than the width of the anode current collector layer 11 and the cathode current collector layer 13. The total thickness of a battery cell ranges from about 100 um to 5000 um. The length or width vs. thickness ratio of the battery cell ranges from 10 to 10. 6 The thickness direction is the vertical direction from the anode current collector layer 11 and the cathode current collector layer 13 in the figure. The width of the frame area of ​​the separator layer 12 is greater than the width of the sealing part, and the permeation area of ​​the porous area is greater than the cathode area.

[0042] like Figure 5 , Figure 6 As shown, multiple battery cells 1 are stacked in the same direction, that is, the anode current collector layers 11 and cathode current collector layers 13 of adjacent battery cells are attached to each other and connected in series, so that the series connection between the battery cells 1 will form a unit group, and the gaps around the battery cells 1 are filled with an insulating layer 2 ( Figure 6 The insulating layer 2 is filled at the edges between the battery cells to isolate the stacked high-voltage batteries. The material used for the insulating layer can be a polymer with a high shrinkage rate, that is, it is elastic, which can compensate for the expansion of the battery cells, for example, a rubber-type polymer, EPDM, or silicone rubber.

[0043] like Figure 7 As shown, when multiple cell groups are stacked, that is, when the bipolar zinc ion battery contains two or more cell groups, the cell groups are stacked along the stacking direction of the battery cell 1, and an insulating layer 2 is provided between adjacent cell groups, and the cell groups are connected in parallel through the current collector 3. Figure 6 The specific assembly structure of the unit group in Figure 5Similarly, the insulating layer at the gaps around the cell group is not shown in the figure. A stainless steel frame 4 is also provided around the insulating layer 2 in the stacking direction to prevent the battery from expanding along the stacking direction of the cell group. The insulating layer in the stacking direction needs to absorb the expansion of the cell group stack and avoid short circuit. It can be EPDM rubber, PE, PBT, PET, PP, PVC, etc. The plastic current collector can be doped or electroplated with copper, aluminum, nickel or carbon nanotube composite materials or any combination of the above materials. In a cell group, there can be 2-1000 single-layer battery cells stacked, and the voltage of the cell group can be as high as 2000V.

[0044] The following describes the method of manufacturing a battery cell.

[0045] Method 1

[0046] The cathode powder, conductive agent and binder are made into thin sheets by double-screw extrusion, rolled to increase density, and attached to the plastic current collector by thermal compounding to form the cathode electrode sheet; similarly, the anode sheet is made in the same way. Then, the cathode sheet, diaphragm paper and anode sheet are laminated and compounded. During the lamination process, the electrolyte is sprayed and sealed in the frame area to finally form a battery cell. The battery cells are laminated to form a battery pack.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A bipolar zinc ion battery, characterized in that: comprising at least one cell group, the cell group comprising at least one battery cell; The unit group includes at least one battery cell; the battery cell includes: an anode plastic current collector, a separator and an anode plastic current collector which are stacked in sequence and sealed with each other on all sides to form two cavities, a cathode active material layer arranged on the inner side of the cathode current collector as a cathode, an anode active material layer arranged on the inner side of the anode current collector as an anode, an electrolyte infiltrated in the gaps between the cathode, the anode and the separator, which contains a zinc compound, and a porous ion channel arranged on the separator between the cathode and the anode for the movement of zinc ions; The electrolyte uses pure water as a solvent, and O2 and H2 released during the charge and discharge process can penetrate the anode plastic current collector and the anode plastic current collector, while water cannot penetrate the anode plastic current collector and the anode plastic current collector; The isolation membrane includes a porous channel region located in the middle and containing the porous ion channel, and a frame region located around the porous ion channel region. The area of ​​the isolation membrane is larger than the anode collector layer and the cathode collector layer, so that the frame region is exposed to the anode collector layer and the cathode collector layer on all sides after being bonded to the anode collector layer and the cathode collector layer.

2. The bipolar zinc ion battery according to claim 1, wherein The inner side of the anode current collector layer is coated or electroplated with an anode material layer containing zinc powder or zinc alloy or a zinc foil layer as an anode.

3. The bipolar zinc ion battery according to claim 2, wherein: The surface of the zinc foil layer or the surface of each particle of the zinc powder is coated with an organic coating layer or an inorganic coating layer, or a coating layer mixed with organic and inorganic substances.

4. The bipolar zinc ion battery according to claim 1, wherein: The cathode active material contains nano manganese tetroxide particles, and / or the cathode active material is doped with Ni, Co, Al, Mg, Fe, V or Cu, and the surface of the manganese tetroxide particles is coated with a carbon nanotube layer, a carbon layer or a graphene layer, and the carbon layer, the carbon nanotube layer or the graphene layer forms a three-dimensional network structure, connecting all the nano manganese tetroxide particles.

5. The bipolar zinc ion battery according to claim 1, wherein: The area of ​​the porous channel region is larger than the area of ​​the anode and the cathode, so that the periphery of the porous channel region exceeds the periphery of the cathode and the anode opposite thereto.

6. The bipolar zinc ion battery according to claim 5, characterized in that: The isolation membrane is made of a porous substrate, and the frame area is made of a porous substrate filled with a polymer or by heat treatment to close the original porous channel area to form a frame area.

7. The bipolar zinc ion battery according to claim 2, wherein: The anode current collector layer and the cathode current collector layer are coated with conductive pre-coating layers for bonding the anode material and the cathode material, respectively.

8. The bipolar zinc ion battery according to claim 1, wherein: When the unit group includes two or more battery cells, the anode current collector layers and cathode current collector layers of adjacent battery cells are attached to each other and connected in series.

9. The bipolar zinc ion battery according to claim 1, wherein: When the bipolar zinc ion battery comprises two or more unit groups, the unit groups are stacked along the stacking direction of the battery cells, and an insulating layer is provided between adjacent unit groups, and all unit groups are connected in parallel via current collectors.

10. The bipolar zinc ion battery according to claim 9, characterized in that: The periphery of the bipolar zinc ion battery is provided with a metal outer hoop layer to prevent the battery from expanding along the stacking direction of the cell group, and the portion of the metal outer hoop layer in contact with the cell group is provided with an insulating layer.

Citation Information

Patent Citations

  • Battery

    CN104253283A

  • Bipolar zinc ion battery and preparation method thereof

    CN106898825A

  • Bipolar battery design

    CN107851747A

  • Bipolar zinc ion battery

    CN210897526U